Escherichia coli Meningitis after Rotavirus Gastroenteritis in an Infant. (21st September 2016) - Ozgurhan, Gamze; Vermezoglu, Oznur; Ocal Topcu, Didem; Karbuz, Adem; Vehapoglu, Aysel; Hacihamdioglu, Bulent
Abstract : Although rotavirus gastroenteritis is quite common in the pediatric population, secondary bacterial sepsis following rotavirus infection is a rare clinical entity. Gram-negative bacilli are the fifth most common cause of meningitis in infants but this infection rarely occurs after gastroenteritis. Here, we report a 2.5-month-old infant who developed Escherichia coli ( E. coli ) meningitis after acute rotavirus gastroenteritis. The 2.5-month-old male infant with fever, vomiting, and watery diarrhea that started 1 day earlier was admitted to the hospital. Rotavirus antigen in stool sample was positive. He was hospitalized, and fever was measured at 39.5°C on the second day. Lumbar puncture was done for suspicion of meningitis, and cerebrospinal fluid (CSF) findings suggested meningitis. Intravenous vancomycin and cefotaxime were started empirically. Since E. coli reproduction was seen in blood culture and CSF culture, treatment was continued with cefotaxime. The patient was discharged with minimal midlevel hydrocephalus findings in cranial ultrasonography and magnetic resonance imaging following 21 days of antibiotics treatment. Septicemia development following rotavirus gastroenteritis is an extremely rare clinical condition. It is vital to start prompt antibiotic treatment as soon as the diagnosis of secondary bacterial infection is made because of high mortality and morbidity rates.